Making Immigrants into Criminals: Legal Processes of Criminalization in the Post-IIRIRA Era. (September 2017) - Abrego, Leisy; Coleman, Mat; Martínez, Daniel E.; Menjívar, Cecilia; Slack, Jeremy
During a post-election TV interview that aired mid-November 2016, then President-Elect Donald Trump claimed that there are millions of so-called "criminal aliens" living in the United States: "What we are going to do is get the people that are criminal and have criminal records, gang members, drug dealers, we have a lot of these people, probably two million, it could be even three million, we are getting them out of our country or we are going to incarcerate." This claim is a blatant misrepresentation of the facts. A recent report by the Migration Policy Institute suggests that just over 800, 000 (or 7 percent) of the 11 million undocumented individuals in the United States have criminal records. 1 Of this population, 300, 000 individuals are felony offenders and 390, 000 are serious misdemeanor offenders — tallies which exclude more than 93 percent of the resident undocumented population (Rosenblum 2015, 22–24). Moreover, the Congressional Research Service found that 140, 000 undocumented migrants — or slightly more than 1 percent of the undocumented population — are currently serving time in prison in the United States (Kandel 2016). The facts, therefore, are closer to what Doris Meissner, former Immigration and Naturalization Service (INS) Commissioner, argues: that the number of "criminal aliens" arrested as a percentage of all fugitive immigration cases is "modest" (Meissner et al. 2013, 102–03). The facts notwithstanding, President Trump's fictional tally is important to consider because it conveys an intent to produce at least this many people who — through discourse and policy — can be criminalized and incarcerated or deported as "criminal aliens." In this article, we critically review the literature on immigrant criminalization and trace the specific laws that first linked and then solidified the association between undocumented immigrants and criminality. To move beyond a legal, abstract context, we also draw on our quantitative and qualitative research to underscore ways immigrants experience criminalization in their family, school, and work lives. The first half of our analysis is focused on immigrant criminalization from the late 1980s through the Obama administration, with an emphasis on immigration enforcement practices first engineered in the 1990s. Most significant, we argue, are the 1996 Illegal Immigration Reform and Immigration Responsibility Act (IIRIRA) and the 1996 Antiterrorism and Effective Death Penalty Act (AEDPA). The second section of our analysis explores the social impacts of immigrant criminalization, as people's experiences bring the consequences of immigrant criminalization most clearly into focus. We approach our analysis of the production of criminality of immigrants through the lens of legal violence (Menjívar and Abrego 2012), a concept designed to understand the immediate and long-term harmful effects that the immigration regime makes possible. Instead of narrowly focusing only on the physical injury of intentional acts to cause harm, this concept broadens the lens to include less visible sources of violence that reside in institutions and structures and without identifiable perpetrators or incidents to be tabulated. This violence comes from structures, laws, institutions, and practices that, similar to acts of physical violence, leave indelible marks on individuals and produce social suffering. In examining the effects of today's ramped up immigration enforcement, we turn to this concept to capture the violence that this regime produces in the lives of immigrants. Immigrant criminalization has underpinned US immigration policy over the last several decades. The year 1996, in particular, was a signal year in the process of criminalizing immigrants. Having 20 years to trace the connections, it becomes evident that the policies of 1996 used the term "criminal alien" as a strategic sleight of hand. These laws established the concept of "criminal alienhood" that has slowly but purposefully redefined what it means to be unauthorized in the United States such that criminality and unauthorized status are too often considered synonymous (Ewing, Martínez, and Rumbaut 2015). Policies that followed in the 2000s, moreover, cast an increasingly wider net which continually re-determined who could be classified as a "criminal alien, " such that the term is now a mostly incoherent grab bag. Simultaneously and in contrast, the practices that produce "criminal aliens" are coherent insofar as they condition immigrant life in the United States in now predictable ways. This solidity allows us to turn in our conclusion to some thoughts about the likely future of US immigration policy and practice under President Trump.